I Identification of Prospective Physics Teacher's Misconceptions of Temperature and Heat concept Using the Three Tier Test: England - Busyairi, Ahmad; Munandar, Rizky; Apsari, Putu Ayas Dita; Wahyuni, Atika; Nurhasanah, Nurhasanah; Arni, Kurnia Julianti; Walihah, Zahratul; Diarta, Muhammad Hendri (Balai Publikasi Indonesia, 2022)
This study aims to identify the misconception profile of prospective physics teachers (respondents) on the material of temperature and heat. This research is quantitative descriptive research. As many as 25 prospective physics teachers as respondents in this study. The research data was taken using a three-tier test instrument in the form of multiple choice questions with open reasons. The results showed that as many as 58.73% of respondents experienced misconceptions and only 30.82% of respondents understood the concept. Most of the misconceptions occur in the concept of thermal equilibrium. As many as 61.90% of respondents experienced misconceptions about this concept. In addition, many misconceptions occur in differentiating the concepts of temperature, heat, and thermal energy. A total of 59.53% of respondents experienced misconceptions about this concept. the average respondent has not understood the substance of the difference between the concepts of temperature, heat, and thermal energy. Many of them equate to the concept of heat and thermal energy of an object. respondents also do not seem to be very able to distinguish the boundaries between the concept of temperature and the concept of thermal energy.